Contralateral breast cancer: incidence according to ductal or lobular phenotype of the primary. Issue 2 (February 2016) - Langlands, F.; White, J.; Kearins, O.; Cheung, S.; Burns, R.; Horgan, K.; Sharma, N.; Dodwell, D.
Abstract : Aim: To identify differences in the incidence of contralateral breast cancer between patients with a primary tumour diagnosis of invasive ductal carcinoma (IDC) and those with a diagnosis of invasive lobular carcinoma (ILC). Materials and methods: Data from two large cancer registries (registry A & B) the Northern and Yorkshire Cancer Registry Information Service (NYCRIS) and the West Midlands Cancer Intelligence Unit (WMCIU) from 1998–2003 for all cases of invasive breast cancer of either pure ductal or pure lobular reported histology were obtained. The invasive status of the contralateral tumour diagnosis and tumour morphology was collected. Chi-square tests were undertaken to examine the differences in contralateral rates for both registries and univariate analysis to ascertain which predictors affected contralateral breast cancer risk for registry A the WMCIU cases. Results: A total of 38, 132 patients were studied, 32, 735 patients with IDC and 5397 (14.2%) patients with ILC over the 6-year period. There was no significant difference between the occurrence and time to occurrence of contralateral breast cancer according to original cancer histology, 901 (2.8%) patients with IDC versus 166 (3.1%) patients with ILC ( p =0.169). The analysis of registry A cases showed no association between original histology (ductal versus lobular), age at diagnosis, tumour grade, use of radiotherapy for the primary cancer or use of systemic therapy (chemotherapy and/or endocrine therapy), and development of a contralateral breast cancer. Conclusion: There is no apparent increase in risk of developing a contralateral breast cancer according to the primary cancer histology either IDC or ILC. Standard mammographic follow-up does not need to take account of original tumour pathology. Increased intervention or post-treatment surveillance for the contralateral breast is not indicated in the context of ILC. The role of MRI should be restricted to those patients with ILC who are planning breast-conservation surgery, but not for assessing the contralateral breast. Highlights: We compare data from two larges breast cancer registries over five years of invasive breast cancer of either pure ductal or pure lobular. We examined differences in developing a contralateral breast cancer according to the primary cancer histology. There is no apparent increase in risk of developing a contralateral breast cancer between invasive ductal or invasive lobular carcinoma. Increased intervention or post treatment surveillance for the contralateral breast is not indicated in the context of invasive lobular carcinoma. The role of MRI is restricted to those patients with invasive lobular carcinoma who are planning breast conservation surgery but not for assessing the contralateral breast.